Threat But Not Arousal Narrows Attention: Evidence from Pupil Dilation and Saccade Control - Van Steenbergen, Henk; Band, Guido P.; Hommel, Bernhard (Frontiers in Psychology, 2011)
It has been shown that negative affect causes attentional narrowing. According to Easterbrook’s (1959) influential hypothesis this effect is driven by the withdrawal motivation inherent to negative emotions and might be related to increases in arousal. We investigated whether valence-unspecific increases in physiological arousal, as measured by pupil dilation, could account for attentional narrowing effects in a cognitive control task. Following the presentation of a negative, positive, or neutral picture, participants performed a saccade task with a prosaccade versus an antisaccade instruction. The reaction time difference between pro- and antisaccades was used to index attentional selectivity, and while pupil diameter was used as an index of physiological arousal. Pupil dilation was observed for both negative and positive pictures, which indicates increased physiological arousal. However, increased attentional selectivity was only observed following negative pictures. Our data show that motivational intensity effects on attentional narrowing can occur independently of physiological arousal effects.